Preliminary approach about using nowadays knowledge engineering in artificial intelligence: a literature overview - Vegega, Cinthia (2022)
This paper presents a first literature overview on the nowadays use of Knowledge Engineering in the framework of the development of solutions in the field of Artificial Intelligence. With the assumption that the conceptualization, formalization and modeling of data is fundamental in this type of projects, it is considered that Knowledge Engineering can actively collaborate orienting and guiding part of these activities. In this context, a doctoral research line is proposed about the use of Knowledge Engineering to perform Intelligent Data Analysis. This line of research arises from the fact that existing methodologies in the field of Artificial Intelligence and Data Mining do not incorporate complete domain and context knowledge in data analysis. The incorporation of this knowledge allows contrasting the hypotheses obtained from the data and enriches the analysis reaching better results.